Develop new formulation for high performance soft thermal pad - Foo, Shi Rui. (2009)
In the thermal management materials market, there are strong interest and huge demand on thermal pad product, however, the hardness and thermal conductivity of current thermal pad products cannot meet certain requirements for high end electrical devices. In this final year project, we find that the root cause to the hardness and thermal conductivity performance are due to the type/function group of silicone gel used for the matrix and the size/shape/type/amount of the filler added in the matrix affect the hardness as well.